1977
DOI: 10.1128/iai.17.2.430-438.1977
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of babesiosis in BCG-infected mice and its correlation with tumor inhibition

Abstract: Infection of mice with Bacillus Calmette-Guerin (BCG) provided good protection against Babesia species. The intensity and duration of this protection was similar to that established after natural recovery from babesiosis. It developed too soon after the first exposure to the parasite, and was too radioresistant, to be attributable to specific antibody production. In addition, the parasites degenerated within circulating erythrocytes. This phenomenon is inconsistent with phagocytosis or lysis of parasites or pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
20
0

Year Published

1979
1979
2007
2007

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 27 publications
6
20
0
Order By: Relevance
“…Clearly protection afforded by this diverse range of agents is most unlikely to be due to antigenic similarity causing a cross-reacting specific immune response. In view of our results with irradiation and CY described in this paper and elsewhere (Clark et al 1977b) protection is equally unlikely to be mediated by an enhanced specific antibody response. Another possibility is that this protozoan may be very susceptible to the poorly defined non-specific mechanism(s) by which these agents protect against certain other infections, agents and tumours.…”
Section: Discussionsupporting
confidence: 64%
See 4 more Smart Citations
“…Clearly protection afforded by this diverse range of agents is most unlikely to be due to antigenic similarity causing a cross-reacting specific immune response. In view of our results with irradiation and CY described in this paper and elsewhere (Clark et al 1977b) protection is equally unlikely to be mediated by an enhanced specific antibody response. Another possibility is that this protozoan may be very susceptible to the poorly defined non-specific mechanism(s) by which these agents protect against certain other infections, agents and tumours.…”
Section: Discussionsupporting
confidence: 64%
“…As in mice protected against B. microti with BCG (Clark et al 1977b), C. paruum (Clark et al 1977a) or B. abortus S19 (Herod et al 1978) the inclusion bodies shown to be degenerate intra-erythrocytic parasites (Clark et al 1977c) were present in red cells of protected mice in these experiments. The dead parasites had the same appearance and were as common as those previously illustrated by light microscopy (Clark et al 1977a, 1977b, 1977c, Herod et al 1978) and electron microscopy (Clark et al 1977b. Again, parasites could not be detected in macrophages on impression smears from spleens and livers of protected mice.…”
Section: Intra-erythrocytic Death Of B Microti In Protected Micesupporting
confidence: 71%
See 3 more Smart Citations